Implementing explicit pronunciation instruction: The case of a nonnative English-speaking teacher. (May 2023) - Gordon, Joshua
Studies in second language teacher cognition (SLTC) of pronunciation teachers have increased in the last 10 years, due mainly to the fact that the decisions teachers make about explicit instruction are critical for the development of second language (L2) pronunciation in learners. Although recent research has indicated that nonnative-speaking teachers (NNSTs) can be as effective as native-speaking teachers (NSTs) in pronunciation instruction, and that their training needs resemble those of NSTs, the way NNSTs implement L2 pronunciation instruction has not been studied extensively. This is important to understand given the number of NNSTs of English worldwide at present, and because of the potential benefits of nonnative-speaking pronunciation teaching models in general. In this study, I analysed the way an experienced NNST implemented explicit pronunciation instruction in a context of English as a foreign language (EFL) to understand both his actual teaching practices and the rationale behind such practices. Using a framework of knowledge base of language teaching, this study demonstrates how factors such as previous teaching and learning experiences, teaching context, and L2 learner characteristics shaped and guided the techniques the teacher implemented in class. These results are discussed in terms of implications for pronunciation teaching and teacher training purposes.